(untitled) (Journal of Medicine, 2015)
Effective BP control is far away from reality in many patients in spite of advancements in many classes of antihypertensive drug therapy. Use of triple drug combination in the management of hypertension have already been established, however this study was conducted to evaluate the efficacy and safety of triple drug fixed dose combination of Telmisartan 40 mg, Amlodipine 5 mg and Hydrochlorothiazide 12.5mg. 69 hypertensive patients with seating cuff systolic blood pressure e 160 mmHg and diastolic blood pressure e100 mmHg were enrolled in the study. Patients were prescribed to take triple drug fixed dose combination for 120 days. Patients were evaluated on 30th, 60th and 120th days of treatment. There was statistically significant (p<0.0001) decrease in systolic blood pressure from baseline to 30th, 60th and 120th day of treatment mean±SD (166±18.6 mmHg vs.147±16.1, 137±14.7 and 130±13.9 mmHg) respectively. Similar to SBP, decrease in DBP was highly significant (p<0.0001) from the baseline to the 30th, 60th and 120th day of treatment (104±11.5 mmHg vs. 93.7±12.3, 89±10.2 and 84.5±8.98 mmHg respectively). Moreover at the end of the study period of 120 days 85.7% and 87.8% patients of age group >60 years and <60 years respectively achieved the JNC VIII recommended goal. This triple drug fixed dose combination of Telmisartan, Amlodipine and hydrochlorothiazide was found to be effective and safe option for the optimal management of hypertension. DOI: http://dx.doi.org/10.3329/jom.v16i1.22383 J MEDICINE 2015; 16 : 18-22